Correlation between Shanghai crude oil futures, stock, foreign exchange, and gold markets: a GARCH-vine-copula method. Issue 11 (3rd March 2021) - He, Chaohua; Li, Guangchen; Fan, Hai; Wei, Weixian
ABSTRACT: The relationship between markets has always been a topic of heated debate among scholars from various countries. One of the most important concerns is the need to model the relationships between the crude oil market and other markets. Based on daily return observations from 2018 to 2019, we apply a GARCH-vine-copula approach to probe the linkage between Shanghai crude oil futures, stock, foreign exchange, and gold markets. We find that obvious tail dependencies do exist between these markets. And the crude oil futures market occupies a dominant position. Moreover, when the Shanghai crude oil futures market is taken as the known condition, the links between different markets reduce to some extent. Finally, value at risk results denote that the risk of the Shanghai crude oil futures market is relatively high, but portfolio investment can effectively reduce the risk. Moreover, the model fitting results at different confidence levels have passed the Kupiec backtest, indicating that the model in this paper fits the relationship between these markets well.